2007
DOI: 10.1007/s00167-006-0280-x
|View full text |Cite
|
Sign up to set email alerts
|

Levels of biomarkers correlate with magnetic resonance imaging progression of knee cartilage degeneration: a study on canine

Abstract: To examine the association between levers of cartilage oligomeric matrix protein (COMP), matrix metalloproteinases-1 (MMP-1), matrix metalloproteinases-3 (MMP-3), tissue inhibitor of matrix metalloproteinases-1 (TIMP-1) in serum and synovial fluid, and MR imaging of cartilage degeneration in knee joint, and to understand the effects of movement training with different intensity on cartilage of knee joint. 20 adult canines were randomly divided into three groups (8 in the light training group; 8 in the intensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Yet, findings suggested that cartilage thickness has much less ability to adapt to mechanical loading than muscle. Further, findings of Qi and Changlin [33] not only support our results but also reveal the weaknesses of the contradictory ones. According to their study, long-time and high-intensity movement training induces cartilage degeneration in the knee joint.…”
Section: Discussionsupporting
confidence: 89%
“…Yet, findings suggested that cartilage thickness has much less ability to adapt to mechanical loading than muscle. Further, findings of Qi and Changlin [33] not only support our results but also reveal the weaknesses of the contradictory ones. According to their study, long-time and high-intensity movement training induces cartilage degeneration in the knee joint.…”
Section: Discussionsupporting
confidence: 89%
“…76 Regardless, COMP may be diagnostically useful as serum and synovial fluid levels have been shown to correlate with canine knee MRI grades of cartilage lesions. 60 Urinary COMP was also predictive of the presence of osteophytes in racehorses with carpal fractures. 77 Serum COMP concentration was lower in osteoarthritic horses versus normal.…”
mentioning
confidence: 90%
“…Studies have shown strong correlations between these degradative markers and magnetic resonance imaging (MRI) findings. [56][57][58][59][60] Markers associated with bone turnover have also been identified, but they are less commonly considered to be diagnostic markers as these are often altered only during advanced stages of disease. [61][62][63][64] MMPs are zinc-and calcium-dependent enzymes that degrade specific substrates of the ECM and include stromelysins, collagenases, gelatinases, and membrane metalloproteases.…”
mentioning
confidence: 99%